Re-phrasing turf-human relations: opening space to imagine more polite practices with turfgrasses - Egret, Cookie, author; Szymanski, Erika, advisor; Amidon, Tim, committee member; Koski, Tony, committee member (Colorado State University. Libraries, 2021)
This thesis aims to induce wonder and cooperation towards enacting turfgrass formations and discourses in more reciprocal ways. I amplify Kenneth Burke's take on rhetoric as the art of inducing cooperation, but extend this definition to everyday multispecies relations. In the midst of increasingly unpredictable and unstable climatic conditions, it's imperative to collaborate creatively across disciplines, but also with the biotic relations we co-create worlds with. As a scholar in rhetoric and composition, I perform a discursive analysis on an aspect or slice of the myriad discourses enabling and constraining turfgrass practices. I use rhetorical and social studies methods to analyze thirteen scientific articles on turf from the International Turfgrass Society Research Journal. My qualitative research is undergirded by interdisciplinary theories that emphasize material relations and historical conditions. My findings let me theorize that turf is a complex assemblage, currently governed and enacted according to anthropocentric aesthetic principles of aboveground turf canopy quality, uniformity and performance. From this grounded theory, I hope to open space towards cultivating other ways of knowing and attending to turfgrass assemblages that might sustain diverse relations and lifeways. Our interconnected futures depend on a shared ability to respond and become response-able with multispecies others.
Keywords: land; polite; turf; multispecies; care; STS